School Reputation Management for Institutional Sustainability and Achievement of Excellent Predicate - Warta, Waska; Achmad Syam, Rifqi Zaeni; Rahmatullah, Tansah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Reputation is considered a powerful weapon essential in maintaining and preserving an organization's existence. It is also seen as a guarantor for achieving growth amidst turbulence and intense competition among service providers, including in the education sector. School administrators fully recognize the importance of reputation for the existence and growth of educational institutions, but not all of them manage it properly. This study aims to explain the formation of school reputation and analyze the importance of massive implementation of school reputation management. Using a qualitative approach and case study method, data were obtained through interviews, observations, and documentation studies. The research found that all the top, famous, prestigious, and highly reputable high schools in Bandung have not formally integrated reputation as a strategic component, as indicated by the absence of discourse on implementing school reputation management in their environments. So far, reputation management has been natural, not based on strategic plans and tactical measures to counter potential crises that every organization might face. Effective reputation management is crucial for the existence and advancement of leading schools, involving reputational communication strategies, institutional messaging through programs and interactive media, and feedback management to build and maintain the school's reputation.